(untitled) (Journal of Hama University, 2024)
This research aims to evaluate the natural regeneration of some groups of Cupressus sempervirens var horizontalis spread naturally in the Syrian coastal mountain chains. The sites of Cupressus sempervirens var horizontalis were inventoried in the period (2020-2022) to study the factors affecting its regeneration. The number of selected sites was: 13 sites in the regions (Masyaf, Ain Al-kroom, AL-Qadmous, Sheikh Badr, AL-Samra, Goubet barghal). Multilinear Regression and Regression Binary Logistic Model were used to evaluate regeneration in the selected samples. Cupressus sempervirens showed a strong variation in its ability to regenerate in its natural sites, And the results showed a complete absence of its seedlings in many sites. In addition to a heterogeneity of the regeneration in the sites. There was no significant relation between the variables (Canopy covering, shrub covering, basal area, height of site, exposure, Number of mother trees) and regeneration in all samples. The site (Tallah) was characterized by the highest percentage of seedlings per hectare (1750) where the canopy covering was 90%. The site (AL-Maghawry1) had a lack of natural regeneration, where the canopy or shrub covering doesn’t exceed 40%. Multilinear Regression and Regression Binary Logistic analysis showed that 61% of the variations in the lengths of the seedlings were related to the thickness, the wet weight of forest floor and site. also 26% of the variations in seedling circumference depended on the site. The model couldn’t show any effect for the properties of the forest litter in the number of seedling